Analisis daya terima terhadap variasi menu makanan lengkap pada anak usia 1 – 6 tahun - Munifa Munifa; Dhini Dhini (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
Difficulty eating in children often occurs in preschool children by > 20%. Difficulty eating in children is a complex problem. Factors causing malnutrition are nutrition imbalances, factors for providing and serving nutritious food. Acceptance is the level of individual liking or disliking of a type of food. Acceptance test was conducted to determine whether the variation of the food menu was acceptable or not. With the variation of recipe standards on quality and quality standards, among others, by changing the taste of food and the appearance of the food, but still maintaining the nutritional value, it is expected to increase acceptability. This study was conducted to analyze the variation of a complete diet on the acceptance of preschool children in daycare. Experimental research design method is posttest-only control group design. The trial was carried out for 3 days. When this stage is complete, the researcher evaluates its implementation. The intervention given is in the form of 1 toddler lunch cycle. 1 lunch cycle is given for 2 weeks. At the age of 1-3 years, staple foods showed differences in the average intake of 5 types of staple foods and vegetables with a p value of 0.002, animal side dishes 0.003, vegetable side dishes 0.737, and fruit 0.0005. At the age of 4-6 years, staple foods showed differences in the average intake of 5 types of staple foods with a p value of 0.107, animal foods 0.043, plant foods 0.351, vegetables 0.809, and fruit 0.01